2004
DOI: 10.1097/00124509-200403000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Reduces Cognitive Impairment After Electroconvulsive Therapy

Abstract: Our results indicate that cognitive impairments in the early recovery period after ECT are reduced with propofol compared to thiopental anesthesia. We suggest that, in addition to ECT parameters, the type of anesthetic agent should be considered to reduce cognitive impairments after ECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…(6) In Noam's study the dose of thiopentone was 3.6 mg/kg and that of propofol was 1.9 mg/kg. (5) In a pilot study conducted before the present study, in which the dose of thiopentone used was 2 mg/kg, but most of the patient's complaints of awareness during the procedure and show very high haemodynamic fluctuations.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…(6) In Noam's study the dose of thiopentone was 3.6 mg/kg and that of propofol was 1.9 mg/kg. (5) In a pilot study conducted before the present study, in which the dose of thiopentone used was 2 mg/kg, but most of the patient's complaints of awareness during the procedure and show very high haemodynamic fluctuations.…”
Section: Discussionmentioning
confidence: 86%
“…The propofol group shows an increased mean weight compared to thiopentone. Reports by Noam (2004) (5) took the European population with a mean weight around 75.5 kg. The calculated mean dose of thiopentone (T-4 mg/kg) was not needed to attain the anaesthetic plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's a short-acting lipophilic drug that quickly crosses the blood-brain barrier with an onset of action ranging from seconds to minutes 69 . Butterfield et al also reported greater reduction in post ECT cognitive impairment with propofol compared with thiopental when assessing cognitive states 5 minutes after each ECT by applying various neuropsychological tests, including immediate and delay verbal memory 67 , confirming that propofolanaesthesia is less damaging to cognitive function when compared to older anesthetic agents such as thiopental.…”
Section: Prevention Of Neurocognitive Side-effect Of Electroconvumentioning
confidence: 93%
“…5 Propofol is a nonbarbiturate hypnotic agent that is widely used in ECT anaesthesia because of its associated rapid recovery and haemodynamic stability advantages. [6][7][8] Propofol may increase the efficacy of ECT 9,10 and can decrease post-ECT confusion, 11 however, its use is associated with a dose-dependent decrease in seizure duration. 12 Decreasing the dose of propofol is associated with longer seizures, and one means of decreasing the propofol dose (for example to 0.5 mg/kg) is to use it in combination with 1 mg/kg remifentanil.…”
Section: Introductionmentioning
confidence: 99%